Immunogenicity and safety of a high-dose hepatitis B vaccine among patients receiving methadone maintenance treatment: A randomized, double-blinded, parallel-controlled trial. Issue 18 (25th April 2017) - Shi, Jing; Feng, Yongliang; Gao, Linying; Feng, Dan; Yao, Tian; Shi, Shan; Zhang, Yawei; Liang, Xiaofeng; Wang, Suping
Highlights: The high dose (60 μg) recombinant hepatitis B vaccination showed a numerically better immunogenicity than low dose (20 μg) vaccine among the methadone maintenance treatment (MMT) patients. Vaccinated with hepatitis B vaccination, geometric mean concentration (GMC) of anti-HBs among the MMT patients peaked at month 7, and declined at month 12, and GMC of anti-HBs, seroconversion and high-level response rates among the MMT patients decreased over time. Both HIV infection and concomitant drug abuse were signiﬁcant predictive factors for strong response in MMT patients after hepatitis B vaccination. Abstract: Background and aims: To explore whether the immunization with high-dose (60 μg) hepatitis B vaccines in patients receiving methadone maintenance treatment (MMT) could yield a superior protection against hepatitis B infection than did the standard dose (20 μg). Methods: We conducted a randomized, double-blinded, parallel-controlled trial in MMT patients. Patients with serologically negative hepatitis B surface antigen (HBsAg) and hepatitis B surface antibody (anti-HBs) were randomized in a ratio of 1:1 to receive three intramuscular injections of 20 μg or 60 μg recombinant hepatitis B vaccine at months 0, 1, and 6. Serum HBsAg and anti-HBs were measured at months 7 and 12 post-vaccination to assess the immunogenicity. Results: A total of 196 MMT patients were randomized and 195 received at least one injection (98 and 97 in 20 and 60 μg vaccine groups, respectively). The 60 μg vaccine group showed a seroconversion of anti-HBs of 87.3%, high-level response rate of 56.3%, and GMC of 742.9 mIU/mL at month 7. While these results were numerically higher than the 20 μg group, a statistical difference was not found. HIV infection and concomitant drug abuse were negatively associated with the robust immune responses. 7.7% of MMT patients receiving at least one dose of vaccine reported solicited adverse reactions within 7 days after vaccination, 2.6% reported unsolicited adverse reactions within 28 days after vaccination. None of the MMT patients reported serious adverse events or became HBsAg positive during the follow-up. Conclusions: The three-dose regimen of 60 μg recombinant hepatitis B vaccine at months 0, 1, and 6 can yield a similar immunogenicity among MMT patients as compared to the 20 μg vaccine. ClinicalTrials.gov identifier :NCT02991599